TiO2/ZnS/CdS Nanocomposite for Hydrogen Evolution and Orange II Dye Degradation - Václav Štengl; Daniela Králová (International Journal of Photoenergy)
TiO2/ZnS/CdS composites for photocatalytic hydrogen production from water were prepared by homogeneous hydrolysis of aqueous solutions mixture of TiOSO4, ZnSO4, and CdSO4 with thioacetamide. Hydrogen evolution was observed in the presence of palladium and platinum nanoparticles deposited on TiO2/ZnS/CdS composites. The morphology was obtained by scanning electron microscopy, the nitrogen adsorption-desorption was used for determination of surface area (BET) and porosity. The method of UV-VIS diffuse reflectance spectroscopy was employed to estimate band-gap energies of prepared TiO2/ZnS/CdS nano-composites. The photocatalytic activity of the prepared samples were assessed by photocatalytic decomposition of Orange II dye in an aqueous slurry under UV irradiation at 365 nm wavelength and visible light up to 400 nm wavelength. Doped titanium dioxide by the CdS increased band-gap energy and doping with ZnS increased photocatalytic activity. The best photocatalytic activity for H2 evolution shows sample named TiZnCd7 on surface deposited with palladium, which contains 20.21% TiO2, 78.5% ZnS, and 1.29% CdS.